Analisis Semiotika Charles Sander Pierce Pada Poster "Merespon Rimpang Dari Efek Rumah Kaca" karya Bagus Aryajatmiko - Nisa, Puspita Choiru (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2025)
This study aims to analyze the meaning contained in the poster "Merespon Rimpang dari Efek Rumah Kaca" by Bagus Aryajatmiko using Charles Sanders Peirce's semiotic approach. This research employs a descriptive method with a qualitative approach. The purpose of this study is to describe the resistance conveyed in the poster "Merespon Rimpang dari Efek Rumah Kaca" by Bagus Aryajatmiko. The results of this analysis show that the message conveyed in the poster can be understood as a call for solidarity and collective resistance against changes deemed detrimental to society.